Reinterpretasi Kosmologi Pertiwi dalam Penciptaan Seni Lukis Dekoratif Monokromatik Biru - Yulianto; Sugeng Nugroho; Halintar Cokro Padnobo; Martinus Dwi Marianto (Besaung : Jurnal Seni Desain dan Budaya, 2026)
This creative research aims to respond to ecological crises and shift in contemporary cultural orientations by focusing on how the philosophical values of the Pañca Mahābhūta cosmology, specifically the Pertiwi (earth) element, are reinterpreted into the visual language of blue monochromatic decorative painting. The creative process adopts Dharsono Sony Kartika’s circular method, comprising stages of experimentation, contemplation, and execution. Artistic experimentation was conducted through exploring watercolor, reactive dyes, and white ink on paper and cotton fabric to examine layering techniques and visual transparency effects. The novelty of this research lies in the visual articulation strategy of the Pertiwi cosmology, which deconstructs the conventional literal representation of earth as terracotta or brown shades by shifting it into a decorative blue-and-white monochromatic spectrum. The creative outcomes demonstrate that the stylization of flora and fauna forms, combined with blue atmospheric rendering, yields visual characteristics that are contemplative, meditative, and symbolic. The three resulting paintings reveal that Pertiwi is no longer merely represented as a material earth element, but as a metaphor for harmony, sustainability, and spiritual interconnectedness between humanity and nature. This study contributes artistic knowledge regarding the efficacy of a monochromatic decorative approach and media layering techniques as a visual transformation strategy for Nusantara cosmology within contemporary fine art discourse